Fenestrated Endovascular Aortic Repair With Chimney Graft for Thoracoabdominal Aneurysm. (May 2022) - Gaines, Sara; Williamson, Ashley J.; Park, Julie; Babrowski, Trissa A.; Milner, Ross
Thoracoabdominal aneurysms pose technical challenges for endovascular repair due to involvement of visceral and renal vessels. We report a case series of four patients diagnosed with thoracoabdominal aneurysm who underwent complex endovascular repair with Fenestrated Device and chimney grafts (FEVARCh). FEVARCh is a technically feasible approach for repair of thoracoabdominal aneurysms that involve renal, superior mesenteric, and celiac arteries for patients not appropriate for open surgical repair. Further studies are needed to understand the implications of resultant Type 1a endoleaks and strategies to minimize the displacement of the main body graft with adjunct chimneys.